Improved pre‐characterization method for the random walk based capacitance extraction of multi‐dielectric VLSI interconnects. (8th January 2015) - Zhang, Bolong; Yu, Wenjian; Zhang, Chao
Abstract: Accurately extracting capacitances among the interconnects in modern multi‐dielectric technology of integrated circuits is a challenging task. The floating random walk (FRW) algorithm is advantageous for capacitance extraction and has been extended by W. Yu et al . to accurately handle multi‐dielectric structures with a pre‐characterization approach. In this paper, we improve this pre‐characterization approach by permitting the cubic transition domains with three or four‐dielectric layers. The techniques of pre‐characterizing and utilizing these multi‐dielectric transition cubes are proposed. Experiments on the test cases under actual manufacture technologies show that the proposed method brings 13× speedup on average, with affordable memory overhead. The experiments also validate the accuracy of the proposed method and reveal the significant error caused by the dielectric homogenization approach in a commercial FRW solver. Finally, on a machine with 12‐core CPU, the parallel FRW algorithm equipped with the proposed pre‐characterization method demonstrates more than 10× speedup of parallelization. Copyright © 2015 John Wiley & Sons, Ltd.